Konsep Nusyu>z Menurut M. Quraish Shihab dalam Tafsir Al-Misbah dan Relevansinya dengan Tingkat Penceraian dalam Rumah Tangga - S.Nupura, Helmi; Mustaqimah; Daud, Ilyas (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
The main issues studied in this study are: how is M. Quraish Shihab’s interpretation of nusyu>z in the Qur’an, and how is it relevant to the level of divorce in the household. The purpose of this study is to find out the interpretation of M. Quraish Shihab about nusyu>z in the Qur’an. This type of research is library research. Research data sources are divided into: first. Primary data sources include the interpretation of al- Misbah which is the work of M. Quraish Shihab. Second, secondary data sources from books of interpretation, books related to M. Quraish Shihab, scientific journals, theses, research or other sources related to the object of the problem in research. The results of this study are, according to M. Quraish Shihab, nusyu>z is the arrogance of  a wife towards her husband, and nusyu>z tends to be shown to the wife, this is also inseparable from the husband’s position as a leader in the household and earns a living  to meet the needs of his family. So that a wife is required to ful fill all her obligations  as a wife. The relevance to the level of divorce in the household is seen from the phenomenon that occurs in society that the fastest solution and is considered a way to solve problems is divorce. This phenomenon occurs in almost all of Indonesia, among others, due to unful filled economic factors, lack of knowledge of religious knowledge, and the existence of disagreements, making it one of the polemics that triggers rifts in the household, so that the path that can be taken by both parties is divorce.